2004
DOI: 10.1016/j.nuclphysa.2004.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear clustering in processes of relativistic multifragmentation

Abstract: Unique capabilities of emulsion technique are considered as applied to the study of multifragmentation of light stable and radioactive nuclei in peripheral interactions at beam energy of few GeV per nucleon. The importance of this research for the physics of few body nuclear systems and the related problems of nucleosynthesis is noted. New results on dissociation of 7 Be and 22 Ne in very peripheral interactions with emulsion nuclei are presented as an illustration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 6 publications
0
16
0
1
Order By: Relevance
“…Experimental data on the charged topology for the final states of a number of light nuclei have been described in [2,3,4,5,6]. More specific studies were performed for the leading channels like 12 C → 3α [7], 16 O → 4α [8,9], 6 Li → dα [10,11], 7 Li → tα [12], 10 B → dαα [13], and 7 Be → 3 Heα [14]. A collection of appropriate reaction images can be found in [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental data on the charged topology for the final states of a number of light nuclei have been described in [2,3,4,5,6]. More specific studies were performed for the leading channels like 12 C → 3α [7], 16 O → 4α [8,9], 6 Li → dα [10,11], 7 Li → tα [12], 10 B → dαα [13], and 7 Be → 3 Heα [14]. A collection of appropriate reaction images can be found in [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In the 9 Be case, the distribution has peaks which are due to the decay of the 0 + and 2 + states. The distribution for the 22 Ne nucleus is essentially broader, its mean value reflects the growth of the α particle transverse momenta, and the possible contribution from the decay of the 8 Be 0 + state is not significant. Thus, the energy calibration of the angular measurements by the 9 Be nucleus enables one to conclude reliably about the features of internal velocity distributions in more complicated systems of relativistic α particles.…”
Section: The Energy Scale In Nα-particle Systemsmentioning
confidence: 93%
“…Emulsions exposed to relativistic 14 N and 11 B isotopes are being analyzed with the aim to study clustering of these types. A 3 He clustering in 7 Be relativistic excitation is demostrated [14,22]. The next round of research, as to whether this kind of nuclear clustering is revealed in light neutron-deficient nuclei like 8 B and 9,10,11 C is in progress now at the JINR Nuclotron [23].…”
Section: Clustering In Light Nucleimentioning
confidence: 98%
See 1 more Smart Citation
“…More specific studies were performed for the leading channels like 12 C→3α [7], 16 O→4α [8,9], 6 Li→dα [10,11], 7 Li→tα [12], 10 B→dαα [13], and 7 Be→ 3 Heα [14]. A collection of appropriate reaction images can be found in [15,16].…”
Section: Introductionmentioning
confidence: 99%